Expression of chondroitin/dermatan sulfate glycosyltransferases during early zebrafish development. Issue 8 (18th June 2013) - Filipek‐Górniok, Beata; Holmborn, Katarina; Haitina, Tatjana; Habicher, Judith; Oliveira, Marta Bastos; Hellgren, Charlotte; Eriksson, Inger; Kjellén, Lena; Kreuger, Johan; Ledin, Johan
<x xml:space="preserve">Abstract</x> Background: Chondroitin/dermatan sulfate (CS/DS) proteoglycans present in the extracellular matrix have important structural and regulatory functions. Results: Six human genes have previously been shown to catalyze CS/DS polymerization. Here we show that one of these genes, chpf, is represented by two copies in the zebrafish genome, chpfa and chpfb, while the other five human CS/DS glycosyltransferases csgalnact1, csgalnact2, chpf2, chsy1, and chsy3 all have single zebrafish orthologues. The putative zebrafish CS/DS glycosyltransferases are spatially and temporally expressed. Interestingly, overlapping expression of multiple glycosyltransferases coincides with high CS/DS deposition. Finally, whereas the relative levels of the related polysaccharide HS reach steady‐state at around 2 days post fertilization, there is a continued relative increase of the CS amounts per larvae during the first 6 days of development, matching the increased cartilage formation. Conclusions: There are 7 CS/DS glycosyltransferases in zebrafish, which, based on homology, can be divided into the CSGALNACT, CHSY, and CHPF families. The overlap between intense CS/DS production and the expression of multiple CS/DS glycosyltransferases suggests that efficient CS/DS biosynthesis requires a combination of several glycosyltransferases. Developmental Dynamics 242:964–975, 2013. © 2013 Wiley Periodicals, Inc.